Analysis of the Effectiveness of Factors Influencing Students' Learning Attitudes in Tutoring Programs - Oktari, Rici; Ayuni, Despa; Widodo, Arip; Qonitah, Mona; Abnisa, Almaydza Pratama (Thawalib: Jurnal Kependidikan Islam, 2025)
Students' positive attitudes influence academic achievement, while negative attitudes are shaped by social environments, with behaviors ranging from active to passive. This study aims to analyze the effectiveness of factors influencing student attitudes during the learning process at Bimbingan Belajar Bulan Kecil in Curup, Rejang Lebong, Bengkulu. The research method utilized a qualitative approach, incorporating interviews, observations, and surveys. Data validity was ensured through source triangulation, technique triangulation, and confirmability. Research findings show that students’ attitudes received an average score of 2.84, indicating positive behaviors such as politeness, appropriate dress, bringing supplies, and focusing on the material that supports the success of the tutoring program. Student motivation was pretty good, with an average score of 2.65, although parental support requires improvement. Tutor attitudes scored high (2.94), fostering a positive learning atmosphere. The classroom environment was conducive to learning comfort, with an average score of 2.89. Peer influence was relatively positive in terms of learning collaboration, despite occasional distractions. Tutors’ teaching methods were effective (average score 2.81), but student engagement needs to improve. Facilities scored high (2.94), supporting learning comfort. The tutoring frequency of three times a week was considered adequate, although students sometimes felt bored. The schedule on Mondays, Wednesdays, and Thursdays did not interfere with other activities (average score 2.64). However, the two-hour session duration was deemed less effective, with an average score of 1.58, indicating the need to adjust the duration or adopt more interactive methods. In conclusion, students’ attitudes during tutoring sessions fall into the good category; however, improvements are needed in parental support, teaching methods, and session duration adjustments.